Psychotropic Drug Use in Recreational Scuba Divers and its Effect on Severe Narcosis - Krummel, Thierry; Thiery, Alicia; Villain, Marion; Schittly, Bernard; Brouant, Benoit (International Journal of Sports Medicine, 2017)
Recreational scuba diving is no longer reserved for young healthy individuals, and as a result, medical drug consumption is on the rise in the diving population. Due to the possible potentiation of nitrogen narcosis by psychotropic drugs, the latter are hence discouraged and are subject to contraindications for practice. However, there are no available experimental data to support this theoretical assumption. The objective of this study is to investigate whether psychotropic drug users are more at risk of severe narcosis. An online survey was sent to the licensed divers from the East of France registered with the French Underwater Federation. Divers were surveyed regarding their consumption of psychotropic drugs, the occurrence of nitrogen narcosis as well as their respective diver’s curriculum vitae.1 608 divers responded to the survey of which 15.2% confirmed having used psychotropic drugs and 7.8% since they became divers. Overall, 40.0% and 5.5% experienced severe and critical narcosis. In multivariate analysis, neither severe nor critical narcosis was associated with psychotropic drug use (OR 0.97 [0.59–1.57] and 0.76 [0.29–2.00], respectively).In conclusion, despite the recommendations, a significant proportion of divers use psychotropic drugs but do not seem to be more prone to severe narcosis.
Keywords: survey; scuba diving; psychotropic drugs; nitrogen narcosis